Narrative selfies and player–character intimacy in interface games - Waszkiewicz, Agata (Eludamos: Journal for Computer Game Culture, 2023)
This paper discusses the use of selfies in narrative-driven interface games, that is games that place the narrative within fictionalized interfaces resembling those of computers or smartphones, as methods of creating intimacy between the characters and the player, while simultaneously maintaining the player’s separateness as a witness of personal stories, rather than their active actor. The article analyses how inter-character and player–character intimacy and emotional distance can be negotiated through the implementation of selfies into the narrative within interface games. The inherent intimacy of such games, which often tell personal stories of people of marginalized identities, is juxtaposed with the constrictions on the player’s agency—both in the overall gameplay and in their inability to take the selfies themselves. Three games are discussed according to three frameworks used to discuss selfies as noted by Gabriel Faimau (2020): a dramaturgic lens (the selfie as self-presentation), a sociosemiotic approach (the selfie as an art of communication), and a dialectical framework (selfie as a social critique).